2013
DOI: 10.1155/2013/565382
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium Oxychloride as a Novel Mordant for Natural Dyeing of Wool Yarns

Abstract: Zirconium oxychloride, a well-known flame retardant, is introduced as a novel mordant for wool dyeing. This has been indicated by mordanting of wool yarns with zirconium oxychloride in different conditions and then dyeing with madder as a famous natural dye. The tenacity, color coordinates, washing, and light fastnesses of the dyed wool confirmed the positive influence of zirconium oxychloride as a useful mordant for wool dyeing with a low impact on the color coordinates. Further, an appropriate washing and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Tannins are an important group of natural mordants which can be obtained from several sources. 31,32 Myrobalan and pomegranate peel are two important sources of tannins that were employed as natural mordant in this study. The colorimetric, K/S, and fastness properties of the dyed yarns were improved in the presence of mordant and natural mordant illustrated the important effect in this area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tannins are an important group of natural mordants which can be obtained from several sources. 31,32 Myrobalan and pomegranate peel are two important sources of tannins that were employed as natural mordant in this study. The colorimetric, K/S, and fastness properties of the dyed yarns were improved in the presence of mordant and natural mordant illustrated the important effect in this area.…”
Section: Resultsmentioning
confidence: 99%
“…Tannins are an important group of natural mordants which can be obtained from several sources 31,32 . Myrobalan and pomegranate peel are two important sources of tannins that were employed as natural mordant in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The colour fastness properties of cotton fabrics dyed with neutral and alkaline safflower extracts were evaluated in terms of fastness to washing, rubbing, perspiration and light according to the AATCC recommendations as shown in table (2). The obtained dyeing results are found to realize an overall fastness properties ranging from good (3) to very good (4)(5). The colour fastness properties of alkaline safflower extract is observed to be relatively lower than that of neutral extract due to the higher sensitivity of the red colour especially to alkaline treatment (perspiration).…”
Section: (Iii) Colour Fastness Propertiesmentioning
confidence: 93%
“…In recent years there is a great international awareness of environmental and ecological consideration. The health hazards associated with the synthesis and application of synthetic dyes (1,2) has led to the revival of natural dyes (3,4,5) . Natural dyes appear to be the most convenient choice as ecofriendly colourants since they are less or non-toxic, nonpollutant and less hazardous compared with synthetic dyes (6,7,8) Therefore, a lot of studies were made on extraction, characterization and application of natural dyes.…”
Section: Introductionmentioning
confidence: 99%
“…According to research reported in line with textile dyeing by natural dyes, the dyed textiles with natural dyes are not stable enough (Forouharshad et al 2013;Saravanan et al 2012). Therefore, it is necessary to enhance the fastness properties of textiles dyed with natural dyes, the common method being the use of a proper mordant.…”
Section: Mordanting Proceduresmentioning
confidence: 99%